الأساليب المستخدمة لدى محاضري اللغة العربية في تقويم الطلبة في الجامعات الليبية والماليزية :دراسة ميدانية مقارنة - Ibrahem Mohamed Soud Hamton
This study aims at recognizing the methods of evaluation used by the Arabic language professors in Libyan and Malaysian universities. The researcher has chosen four universities in both countries. The four universities chosen from Malaysia are University of Putra Malaysia, International Islamic University, National University of Malaysia and University of Malaya. Similarly, the four universities chosen from Libya are Tripoli University (formerly known as al-Fateh University), (University of Sebha, Sirte University (formerly known as al-Tahaddi University), and University of Benghazi (formerly known as Qaryounis University). The researcher has used the Analytic, descriptive and comparative approaches. All the Arabic language professors in Libyan and Malaysian universities have comprised the population of the study where they were ٣٤٣professors-١١١ professors in Malaysian universities and the rest (٢٣٢) in Libyan universities. Due to the small size of the study sample, the researcher has conducted a comprehensive survey for all the study population. The researcher has used the closed questionnaire which consisted of ٨٣ items distributed among the six aspects of the study. The study results showed that the methods of evaluation: projects, assignments, and extra-curricular activities, have been the most important methods used by the Arabic language professors in Malaysian and Libyan universities. However, while "group discussions, participation and professor notetaking"( as methods of evaluation, were the least used by those professors of Arabic language in the Malaysian universities, the least used methods of evaluation used by the professors of Arabic language, in the Libyan universities were oral and listening tests. The researcher recommends, among other things, that it is necessary to widely activate the "group discussions, class participations and professor note-taking" as well as "oral and listening tests" as methods of evaluation in Malaysian and Libyan universities by the professors of Arabic language. He also recommends the necessity of re-adjusting the teaching class to just accommodate less than twenty students for better evaluation.